PENGARUH EDUKASI TERHADAP TINGKAT PENGETAHUAN IBU TENTANG PENANGANAN DIARE PADA BALITA DI DESA HULU KECAMATAN PANCUR BATU - Sarah Honey Nabasa Sihombing; Harsudianto Silaen (PT. Hasba Edukasi Mandiri, 2026)
Risk factors that can trigger diarrhea are environmental factors, community behavior factors, lack of community knowledge about diarrhea, and malnutrition. Mothers' knowledge plays a major role when diarrhea occurs, such as assessment, control, and prevention techniques. The actions taken by mothers when diarrhea occurs will determine the morbidity in children. Objective: To determine the effect of education on mothers' knowledge of diarrhea management in the upstream village of Pancur Batu subdistrict. Methods: This study was quantitative in nature, using a pre-experimental design with a one-group pretest posttest design and a population of 50 respondents, with a sample size of 50 respondents. The independent variable was diarrhea education for mothers, and the dependent variable was mothers' knowledge level. The statistical test used was the paired sample t-test. Results: There was a significant increase in mothers' knowledge about diarrhea management in toddlers after education, with a significant value of 0.001 (p < 0.05) and showing that the average score of mothers' knowledge about diarrhea management in toddlers increased from a score of 48.30 to 79. Conclusion: Education has a positive effect on increasing mothers' knowledge about diarrhea management in toddlers in Hulu Village, Pancur Batu District. The results of this study indicate that education can improve mothers' understanding of diarrhea management in toddlers.